Preventive Intervention against Helminth Infection through Clean and Healthy Lifestyle Among Children in Samarinda: Intervensi Pencegahan Infeksi Cacing melalui Perilaku Hidup Bersih dan Sehat (PHBS) pada Anak di Samarinda - Hanggara Arifian; Annisa Sabilah; Raodhatul Jannah; Viorina Angelica Hendrawan; Christin Elyana Sonda; Brain Christian Severius Tanod (ANDIL Mulawarman Journal of Community Engagement, 2026)
Background: Earthworm infection (STH) remains a significant global health problem. WHO data (2023) shows that more than 1.5 billion people (24% of the world's population) are infected, with children aged 5–14 years being the most vulnerable group due to the intensity of contact with contaminated soil. Method: This community service activity was carried out through health education using leaflets in two locations: Posyandu Melati Putih and SDN 016 Sungai Pinang. The intervention focused on education on the causes, symptoms, and prevention of STH. Results: The education at Posyandu Melati Putih and SDN 016 succeeded in increasing the community and students' understanding of worms, from the causes, symptoms, to prevention through PHBS and regular deworming, as seen from the active question and answer session. In elementary schools, the post-test results obtained an average score of 88.72%. Conclusion: This education effectively encourages worm prevention by increasing awareness of clean behavior and regular deworming.